Decision Support System for Selecting the Best University for Vocational School Graduates Majoring in Multimedia Using the TOPSIS Method - Febriyanti, Lisa; Febrinazahra, Mahdiyyah; Ramasahdan, Yoga Aditya; Niqotaini, Zatin (Universitas Amikom Yogyakarta, 2025)
Purpose: According to Statistics Indonesia (2023), there are around 1.6 million vocational secondary school (SMK) graduates in Indonesia, over 30% of whom come from the Information and Communication Technology field, particularly the Multimedia major. However, more than 40% of them do not proceed to higher education (Tracer Study, Kemendikbud Ristek, 2023), partly due to difficulties in selecting universities that align with their practical skills. This study aims to develop a decision support system that helps Multimedia graduates choose higher education institutions that match their vocational background.Methods/Study design/approach: The study applies the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, using six evaluation criteria: program accreditation, multimedia facilities, industry partnerships, alumni reputation, tuition fees, and internship opportunities. Data were gathered from official secondary sources such as BAN-PT and PDDikti. The TOPSIS method was then used to rank university alternatives based on weighted criteria.Result/Findings: The highest-scoring alternative obtained a preference score of 0.6968, representing an institution with superior accreditation, strong industry collaboration, and complete multimedia infrastructure. Sensitivity analysis showed consistent rankings for some alternatives, while others shifted depending on changes in criteria weights.Novelty/Originality/Value: This study offers a replicable and adaptable decision support system that enables vocational school graduates to make informed, data-driven decisions in selecting relevant higher education pathways. The framework can be customized for other vocational fields or regional applications, providing practical value for both students and education planners.